Perceived parenting stress in the course of postpartum depression: the buffering effect of maternal bonding - Reck, Corinna; Zietlow, Anna-Lena; Müller, Mitho; Dubber, Star (Archives of women's mental health, 2016)
Research investigating maternal bonding and parenting stress in the course of postpartum depression is lacking. Aim of the study was to investigate the development and potential mediation of both constructs in the course of postpartum depression. n = 31 mothers with postpartum depression according to DSM-IV and n = 32 healthy controls completed the German version of the Postpartum Bonding Questionnaire and the Parenting Stress Index at two measuring times: acute depression (T1) and remission (T2). At T1, the clinical group reported lower bonding and higher parenting stress. Bonding was found to partially mediate the link between maternal diagnosis and parenting stress. Furthermore, the clinical group reported lower bonding and higher parenting stress averaged over both measurement times. However, at T2, the clinical group still differed from the controls even though they improved in bonding and reported less parenting stress. A significant increase of bonding was also observed in the control group. Maternal bonding seems to buffer the negative impact of postpartum depression on parenting stress. The results emphasize the need for interventions focusing on maternal bonding and mother-infant interaction in order to prevent impairment of the mother-child relationship.